P116 Basic characteristics of adipose-derived mesenchymal stem cells of ankylosing spondylitis patients. (March 2019) - Kuca-Warnawin, E; Skalska, U; Plebanczyk, M; Janicka, I; Musialowicz, U; Bonek, K; Głuszko, P; Kontny, E
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: Application of mesenchymal stem/stromal cells (MSCs), endowed with immunosuppressive and regenerative properties, may be promising option for successful therapy of ankylosing spondylitis (AS) patients, characterised by inflammation and pathological bone remodelling. Adipose tissue is an easily accessible, rich source of MSCs. Biology of MSCs in AS is poorly understood and data describing MSCs from adipose tissue (ASCs) are missing. Objectives: The aim of this study was to perform comparative basic characterisation of ASCs of AS patients (AS/ASCs) and ASCs line originating from healthy volunteers (hASCs). Methods: AS/ASCs of 15 AS patients and commercially available hASC lines were used. Phenotype and expression of adhesion molecules (ICAM-1, VCAM-1) on ASCs were evaluated by flow cytometry. Basal and cytokine (tumor necrosis factor +interferon g or interleukin-23)-induced secretion of nine factors (TGFß, IL-6, galectin, LIF, IL-1Ra, PGE2, sHLA-G, TSG6 and kynurenines) known to mediate immunomodulatory activity of MSCs was measured by ELISAs. ASCs were co-cultured with either anti-CD3/CD28-stimulated CD4 + T lymphocytes or mitogen-stimulated peripheral blood mononuclear cells (PBMCs) of allogeneic healthy volunteers. Expression of activation markers (HLA-DR, CD25, CD69) on T cells and these cells proliferation were evaluated by flow cytometry. Results: There were no significant differences in the phenotype, expression of adhesion molecules and secretory potential between hASCs and AS/ASCs. Inhibition of T cell proliferation was found in both co-culture systems, while modulation of activation markers expression (CD25 down-regulation, CD69 up-regulation) on CD4 + T and CD8 + T cell subsets was stated in ASCs-PBMCs co-cultures only and hASCs and AS/ASCs exerted similar effects. Conclusions: AS/ASCs have phenotype and basic biological features (i.e. secretory potential, some attributes related to immunomodulatory activities) comparable to hASCs. Acknowledgements: This work was supported by the National Science Centre in Poland (Grant No. 2016/21/B/NZ5/00500) and by the NIGRiR Statutory Grant (Grant No. S/6). Disclosure of Interest: None declared.